Local Hybrid Density Functional for Interfaces - Borlido, Pedro; Marques, Miguel A. L.; Botti, Silvana (Journal of Chemical Theory and Computation, 2018)
Hybrid functionals are by now the state-of-the-art for the calculation of electronic properties of solids within density functional theory. The key to their performance is how a part of Fock exchange is mixed with a semilocal exchange-correlation functional. The choice of the mixing parameter is particularly critical in nonhomogeneous systems, such as an interface between two solid phases. In this work we propose a (non) local mixing function that is a functional of the electron density through an estimator of the local dielectric function. Using this mixing function to modify the PBE0 and the HSE06 hybrid functionals, we obtain band gaps and band-edge alignments at interfaces with an accuracy that is comparable to the one of the GW approximation. However, and in contrast to GW and other recent self-consistent schemes for the mixing parameter, our approach does not require the evaluation of the dielectric function and leads to a negligible increase of the computation time with respect to standard PBE0 or HSE06 hybrid calculations.
CRIS-Team Scopus Importer:2023-04-20